2019
DOI: 10.1016/j.isci.2019.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Object Recognition Based on Fine-Scale Stimulus Timing in Drosophila

Abstract: Summary Odorants of behaviorally relevant objects (e.g., food sources) intermingle with those from other sources. Therefore to determine whether an odor source is good or bad—without actually visiting it—animals first need to segregate the odorants from different sources. To do so, animals could use temporal stimulus cues, because odorants from one source exhibit correlated fluctuations, whereas odorants from different sources are less correlated. However, the behaviorally relevant timescales of tem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 83 publications
3
31
0
Order By: Relevance
“…We found that stimulus onset asynchronies of 5 seconds or more improved odor-background segregation, while stimulus onset asynchronies of 1 seconds or less did not. This timescale for segregating unknown odorants based on stimulus onset asynchrony is at least two orders of magnitude slower than for segregating known odorants (Baker et al, 1998;Sehdev et al, 2019;Szyszka et al, 2012). These results suggest that the neural mechanisms for odor-background segregation based on stimulus onset asynchrony differ for known and unknown odorants.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…We found that stimulus onset asynchronies of 5 seconds or more improved odor-background segregation, while stimulus onset asynchronies of 1 seconds or less did not. This timescale for segregating unknown odorants based on stimulus onset asynchrony is at least two orders of magnitude slower than for segregating known odorants (Baker et al, 1998;Sehdev et al, 2019;Szyszka et al, 2012). These results suggest that the neural mechanisms for odor-background segregation based on stimulus onset asynchrony differ for known and unknown odorants.…”
Section: Discussionmentioning
confidence: 81%
“…Because stimulus onset asynchrony can improve odor-background segregation for known target odorants (Andersson et al, 2011;Baker et al, 1998;Hopfield and Gelperin, 1989;Sehdev et al, 2019;Szyszka et al, 2012), we asked whether mixing A with an asynchronous background would still impair the recognition of A in a mixture with B. We presented B for 30 s and added a 7 s long target odorant A after 20 s (B20A; Fig.…”
Section: Figure 1 Mixing An Unknown Odorant a With A Background Odormentioning
confidence: 99%
See 3 more Smart Citations